STUDENTS' PREPAREDNESS LEVEL TO FACING AN EARTHQUAKE DISASTER IN YOGYAKARTA, INDONESIA: A CROSS-SECTIONAL STUDY - Sahayati, Sri; Rahmuniyati, Merita Eka; Mardani, Sindy (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: Sleman Regency has areas prone to natural disasters such as volcanic eruptions, droughts, earthquakes, and landslides. Faculty of Health Sciences Universitas Respati area has never been assessed for earthquake disaster preparedness, even though it is not exempt from disaster threats. With high preparedness it is hoped that it can minimize the risks due to disasters. Purpose: To find out the level of preparedness of students in dealing with earthquake disasters. Methods: The research design was cross-sectional, with a population of all Faculty of Health Sciences Universitas Respati Yogyakarta students. Samples were taken using the Proportionate Stratified Sampling technique, so a sample of 95 respondents was obtained. The research instrument was from the LIPI/UNESCO questionnaire, 2006. Data analysis used univariate with a quantitative descriptive approach. Results: The index value of earthquake disaster preparedness for students of the Faculty of Health Sciences, University of Respati Yogyakarta has an index value of 84 which is included in the high category. Conclusion: The level of earthquake disaster preparedness among students of the Faculty of Health Sciences, Respati University, Yogyakarta. generally included in the high category with several aspects of preparedness still in the low category such as disaster warning and the ability to mobilize resources.